2022
DOI: 10.3389/fenrg.2022.819939
|View full text |Cite
|
Sign up to set email alerts
|

Simulation and Study of PEMFC System Directly Fueled by Ammonia Decomposition Gas

Abstract: Ammonia can be stored as a liquid under relatively easy conditions (Ambient temperature by applying 10 bar or Ambient pressure with the temperature of 239 K). At the same time, liquid ammonia has a high hydrogen storage density and is, therefore, a particularly promising carrier for hydrogen storage. At the same time, the current large-scale industrial synthesis of ammonia has long been mature, and in the future, it will be possible to achieve a zero-emission ammonia regeneration cycle system by replacing exis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Likewise with the AFC, however, if the performance of SOFCs fueled by ammonia is very similar to that of a hydrogen-fueled one, then the AFC performance is rather low [129]. On the other hand, ammonia poisons PEM cells [130]. On this basis, it can be concluded that in order to use NH 3 in AFC or PEMFC systems, additional components are required to enable proper fuel processing.…”
Section: Selected Methods Of Supplying Fuel Cells With Ammoniamentioning
confidence: 99%
“…Likewise with the AFC, however, if the performance of SOFCs fueled by ammonia is very similar to that of a hydrogen-fueled one, then the AFC performance is rather low [129]. On the other hand, ammonia poisons PEM cells [130]. On this basis, it can be concluded that in order to use NH 3 in AFC or PEMFC systems, additional components are required to enable proper fuel processing.…”
Section: Selected Methods Of Supplying Fuel Cells With Ammoniamentioning
confidence: 99%
“…Electrolytic cell device has a high energy conversion efficiency and a low cost of hydrogen production, making it the most common method for industrial hydrogen production. The real-time hydrogen production of the electrolysis cell can be expressed as [41],…”
Section: Electrolytic Cell Unitmentioning
confidence: 99%
“…If ammonia is used as a hydrogen storage media onboard, more equipment for fuel processing such as a cracker and purifier have to be considered for ammonia's catalytic decomposition and the purification of residual ammonia to deliver pure hydrogen into the PEMFC [52]. Thus, the efficiency of the auxiliaries has to be considered once calculating the ammonia consumption as shown in Equation (2).…”
Section: Fuel Cell System Scenariomentioning
confidence: 99%